Athlete participation an travel to compete: motivations in open-water swim events - Hench, K. E. (ProQuest Dissertations Publishing, 2019)
The underlying basis for the desire to participate is rooted in an individual`s motivation. Understanding athlete participants` motivators are key for race host sites, race promoters, and sport-specific sponsors who seek to distinguish their events in a growing sports tourism market. Absent participant-centered event-specific data related to open-water swimming (OWS) leave race directors and community planners with no clear method of estimating the economic impact of an annual OWS event sports-tourism program. A quantitative, correlational study using multiple regression analyses was performed to assess the intrinsic and extrinsic motivators that drove athlete`s participation intentions and actual participation of athletes in non-traditional mass participation sporting event (MPSE) openwater events throughout the United States. For this study, 160 participants participated in a survey drawn from a sample obtained from individuals who participated in OWS races in the past across the United States. Participants took two surveys that addressed both competition and motivation factors, as well as destination factors. Purposeful sampling was used to ensure the generalizability of the survey results. Multiple regression analysis was used to determine if the factors of the PMQ could predict the factors of the TCS. The results of this study indicated that the motivating factors of sports events, sports action with friends, fitness and health, and popularity indicated strong relationships in travel motivations. These individual participant motivators related to OWS, specifically the motivating factors of sports events, sports action with friends, and fitness and health, and popularity, can assist event organizers and host officials with their race events and in the decision-making process. These new data can aid critical stakeholders in the open-water swim MPSE community in understanding their athletes and in making informed decisions regarding the motivators that drive athlete participation intentions and the actual participation of athletes in non-traditional MPSE open-water events.